GPS performance in the quantification of integrated water vapor in Amazonian regions - Sapucci, Luiz Fernando [UNESP]; Monico, João Francisco Galera [UNESP]; Plana-Fattori, Artemio; Machado, Luiz Augusto Toledo; Lima, Wagner Flauber Araujo (My University, 2004)
The Amazonian regions are characterized by large space-time variability in the humidity fields due to the intense convective process in those areas associated with the great humidity potential generated by high temperatures. An experiment denominated RACCI/DRY-TO-WET (RAdiation, Cloud, and Climate Interactions in the Amazonia during the DRY-TO-WET Transition Season) was carried out in the Brazilian Amazonian Region in 2002. The IWV values from GPS and other techniques, such as radiosondes, radiometer and humidity sounding satellites were used in this experiment to supply subsidies to evaluate the aerosols influence in the associated processes modifications to seasonality of atmospheric water vapor. Those regions are one of the most humid of the planet, where IWV (Integrated Water Vapor) average values are in the order of 50 kg/m2. As according the literature the IWV quantification using GPS has not been explored in those circumstances, the objective this paper is to present the preliminary results obtained in the evaluation of the GPS performance in Amazonian Regions when comparing with other techniques. The tendency measurement values indicated that the IWV values from GPS tend to be larger than those from radiosondes and smaller than those from radiometer. On the other hand, IWV values from GPS are very close of the average values supplied by radiosondes and radiometer. Due to the great amount of atmospheric water vapor existent in this region, the results obtained in the experiment in percentile terms are quite better than those found in the literature, which are around of 10%.
Keywords: Biosensors; Climatology; Clouds; Ecology; Geographical regions; Radiation; Vapors; Amazonian regions; Meteorological models; Quantification; Water vapors; Global positioning system